Supporting multi-step annotation to promote reflective learning: triggered by a cell-phone. (31st July 2008) - Matsuura, Kenji; Gotoda, Naka; Niki, Keiji; Kanenishi, Kazuhide; , Yoneo Yano
Many universities officially permit their students to use cell-phone as an input device in lectures. Considering this situation, this paper proposes a multi-step annotation function using a cell-phone as the trigger to start reflective learning. Using the proposed system during the lecture, students are required to mark the important slides via the cell-phone e-mail. This e-mail is synchronised to the respective slide automatically through the time stamp. Then, the student has to fulfil the annotation content marked by the e-mail after the lecture. This paper describes the design and development of the system, including the observed results of trial uses.